About Hegel’s philosophy of law: questions and objections (Polis (Santiago), 2018)
The author undertakes in this article one of the most cited and controversial work of Hegel of his mature period which is the Principles of Philosophy of Law or Natural Law and Political Science, commonly known as Philosophy of Law, and develops some issues that remain as questions open to debate or as objectionable aspects, both in his theory of objective spirit as in its interpretation.
Keywords: Philosophy of Right; Hegel; objective spirit; ethics